Organic Contaminants in Portland Cements Used in Monitoring Well Construction. Issue 4 (12th December 2014) - Smith, Bert; Siegel, Donald; Neslund, Charles; Carter, Charles
Abstract We report the results of two independent laboratory investigations to evaluate total and leachable concentrations of glycols, glycol ethers, phenol, and other compounds in representative Type I and Type I/II Portland cement products that United States Environmental Protection Agency (EPA), The American Society of Testing and Materials (ASTM) and others recommend as annular sealants in monitoring well completions. Water well drillers also use these cements in their well completions. The EPA has included some of these compounds for analysis in their National Hydraulic Fracturing Study to evaluate the effects of hydraulic fracturing on ground‐ and surface water resources. During any contaminant investigation, materials used in monitoring or water well drilling, completion, development, and sampling must be free of the chemicals being targeted by the regulatory agency. Three of five bulk cement products we tested contained part per million (ppm) (mg/kg) concentrations of diethylene glycol, ethylene glycol, tetraethylene glycol, and triethylene glycol; chemicals added as grinding aids during manufacture. Some cements also contained ppb (µg/kg) concentrations of benzoic acid, phenols, propylene glycol, and 2‐butoxyethanol. Leaching of cured cement samples in water produced ppm (mg/L) concentrations of glycols in the supernatant. These results show that cured cements in monitoring or water wells can contaminate groundwater samples with glycols and phenol. Our findings should help prevent future sample bias and false positives when testing for glycol compounds and phenol in groundwater samples from monitoring or water wells and highlight the need to test materials or products used in monitoring or water well drilling, completions, development, and sampling to avoid false positives when sampling and analyzing for less common analytical constituents.